University Students’ Preferable Types of Teacher Humor in English Classes - Pham Trut Thuy; Le Thanh Thao (Vision: Journal for Language and Foreign Language Learning, 2021)
The current study aimed to explore what types of teacher humor EFL students prefer in their classes. The study was designed as a mixed-method approach, using questionnaires and semi-structured interviews to collect data in two different Vietnamese universities. One hundred fifty-eight university students responded to the survey, and eight out of them were recruited as the participants for the interviews. The study results revealed that the types of jokes (M=4.41), riddles (M=4.08), and language play (M=4.15) were most favored. Besides, the participants' demographic information, including their gender and majors, affected their preferable types of teacher humor. Specifically, males showed more positive attitudes towards teacher humor than their counterparts. In terms of students’ majors, there were differences between non-English majors and English-majored students’ perceptions of irony, teasing, language play, visual and physical humor. Regarding the students’ positive attitudes towards teacher humor, EFL teachers should learn more about valuable strategies for using teacher humor in their classes due to the fact that they do not need to have a sense of humor to use it effectively.